GnRH I and II up-regulate MMP-26 expression through the JNK pathway in human cytotrophoblasts - Wu Xiao-qiu; Li Yu-xia; Cao Bin; Liu Jing; Wang Yan-ling (BMC, 2010)
Abstract Background Matrix metalloproteinase-26 (MMP-26), one of the main mediators of extracellular matrix (ECM) degradation, has been shown to exist in trophoblasts of human placenta and to play a role in trophoblast cell invasion. However, little is known about the regulation of MMP-26 expression in human trophoblasts. Recently, gonadotropin-releasing hormone I (GnRH I) and GnRH II have been shown to regulate the expression of MMP-2, MMP-9/tissue inhibitor of metalloproteinases 1 (TIMP-1), and urokinase plasminogen activator (uPA)/plasminogen activator inhibitor (PAI) in human trophoblasts, suggesting that these two hormones may work as paracrine and/or autocrine regulators in modulating the activities of various protease systems at the feto-maternal interface. In this study, we determined the regulatory effects of GnRH I and GnRH II on the expression of MMP-26 in human immortalized cytotrophoblast-like cell line, B6Tert-1. Methods Real-time PCR was used to quantify mRNA levels of MMP-26 in human trophoblast-like cell line, B6Tert-1 and primary cultured cytotrophoblasts. Western blotting was used to characterize the expression of MMP-26 and the phosphorylation of c-Jun NH2-terminal kinase (JNK) and extracellular signal-regulated kinase 1/2 (ERK1/2) in B6Tert-1 cells after treatment with GnRH I and GnRH II. Results We found that GnRH I increased MMP-26 expression in B6Tert-1 cells after 12 h of treatment at both the mRNA and protein level, while GnRH II increased MMP-26 expression beginning at 3 h of treatment. Treatment of GnRH I at 1 nM resulted in maximal increase of MMP-26 mRNA and protein levels, whereas GnRH II treatment at a concentration of 100 nM was required to induce maximal increase in MMP-26 expression. In addition, we demonstrated that the activation of JNK, but not ERK1/2, was required for GnRH I and II-stimulated MMP-26 production in B6Tert-1 cells and primary cytotrophoblasts. Conclusions These novel findings indicated that GnRH I and II could up-regulate MMP-26 expression through the JNK signaling pathway in human trophoblast-like/trophoblast cells.